The Effects of Using Organic and Biological Fertilizer Along with Lower Rate of Chemical Nitrogen Fertilizer on Quality and Quantity of Rice Yield - Norollah Kheyri; Yousof Niknejad; Maryam Abbasalipour (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2018)
To investigate the possibility of increasing the quantity and quality rice yield (var. Tarom Hashemi) by application of organic and biologic fertilizers with lower rate of chemical nitrogen fertilizer, a field experiment was carried out in a randomized complete block design with eight treatments and three replications in Amol in 2014-2015. Experimental treatments were: T1: control or no fertilizer application, T2: nitrogen fertilizer application of 46 kg.ha-1, T3: azolla compost application of 10 ton.ha-1, T4: vermicompost application of 10 ton.ha-1, T5: nitrogen fertilizer of 23 kg.ha-1 + azolla compost of 5 ton.ha-1, T6: nitrogen fertilizer of 23 kg.ha-1 + vermicompost of 5 ton.ha-1, T7: azolla compost of 5 ton.ha-1 + vermicompost of 5 ton.ha-1 and T8: nitrogen fertilizer of 12 kg.ha-1 + azolla compost of 5 ton.ha-1 + vermicompost of 5 ton.ha-1. Results showed that the percent of sterile floret per panicle increased (13.95%) by not using fertilizer. The highest panicle length (25.47 cm), number of fertile tiller per hill (18.30) and filled grain number per panicle (136.1) belonged to treatment no. T8. Treatments of T3 and T4 resulted in highest 1000-grain weight. The highest grain yield (5295 kg.ha-1) was produced by combined application of nitrogen fertilizer, azolla compost and vermicompost. This was due to the increased panicle length and yield components such as number of fertile tiller per hill and filled grain number per panicle. Amylose content decreased under the combined treatments. The optimum range of gelatinization temperature (ranging between 3 to 5) were observed only in treatments containing chemical nitrogen fertilizer. According to the results of this research, the treatment no. T8, due to reduced nitrogen chemical fertilizer application and its lower environmental impacts was considered to be the best treatment for increasing the grain yield of rice. Although, the combined application of nitrogen with any of the biologic or organic fertilizers, especially azolla, had a significant effect on improvement of seed yield.